(untitled) (Simbiótica. Revista Eletrônica, 2025)
This study empirically examines the game Marvel Snap. It analyzes how the acquisition of digital goods, through the sale of cards and cosmetic items in a virtual store, influences the player’s experience and the social dynamics within the game’s community. Drawing on authors such as Bordieu (2010), Castells (2009), Castro (2012; 2014), Flaganan (2009), Mastrocola (2015; 2016; 2024) and Santaella (2008; 2014; 2015) we investigate how the acquisition of digital goods can confer social distinction in this context. Through non-participatory observation, adapting ideas from Kozinets (2014) on a Reddit page, we conclude that digital goods in games like Marvel Snap play a significant role in constructing the player’s identity and strengthening the gaming community. Therefore, this constitutes a scalable model for the Marvel Snap game, allowing the brand to maximize the commercial potential of its intellectual property.